A Framework for Counsellor-Cultural Broker Collaboration - Brar-Josan, Novjyot; Yohani, Sophie C. (Canadian Journal of Counselling and Psychotherapy, 2014)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 11.0pt; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi;">Cultural differences toward health and help-seeking are among the barriers that refugee youth and families experience when accessing mental health services. Cultural brokering, the act of linking or mediating between different cultural groups, is one potential solution to this service gap. Using a qualitative case study of 2 counsellors and 4 cultural brokers, we present a preliminary framework to facilitate an understanding of, and provide a guide for, collaboration between counsellors and cultural brokers when providing mental health services to refugee youth and families.